Management strategy of large class of PE in primary school / Mohamad Nizam Mohamed Shapie, Mohamad Rahizam Abdul Rahim and Wenyao Chen - Mohamed Shapie, Mohamad Nizam; Abdul Rahim, Mohamad Rahizam; Chen, Wenyao (Universiti Teknologi MARA, 2023)
Classroom management of Large Physical Education (PE) classes is a problem that frontline teachers are particularly concerned about. The purpose is to improve the teaching quality. This study cited 24 relevant literature. I spent 4 years teaching in 2 of the 8 schools I visited on field trips. Ten experts were sequentially interviewed to learn more about how physical education is emerging in large classes. The research results show: 1) The teacher's lax management in the classroom results in poor learning effects and weak teacher authority. 2) Teachers' weak emotional management abilities can't easily lead to students to mobilise their enthusiasm for learning. 3) Long-term marginalisation can easily cause teachers to slack off and no longer pursue personal progress. In order to better manage students on the frontline teachers, the following countermeasures are proposed: First, the card system, team leader system, and reflection system are used in classroom management. Teachers can control the quality and safety well, solve the problem of large class teaching. Second, the cultivation of students' safety awareness not only emphasises theory but also practice, allowing students to participate in management. Third, create a positive classroom environment and serve all students in the classroom. Fourth, help students understand individual differences, formulate personal training plans, and promote healthy physical and mental development.